2009
DOI: 10.5483/bmbrep.2009.42.1.059
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of HBV replication and gene expression in vitro and in vivo with a single AAV vector delivering two shRNA molecules

Abstract: Hepatitis B virus (HBV) infection is highly prevalent worldwide.The major challenge for current antiviral treatment is the elevated drug resistance that occurs via rapid viral mutagenesis. In this study, we developed AAV vectors to simultaneously deliver two or three shRNAs targeting different HBV-related genes. These vectors showed markedly better antiviral effects than ones that delivered a single shRNA in vitro. A dual shRNA expression vector (AAV-157i/1694i), which simultaneously expressed two shRNAs targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Hence, HBV is assumed to be susceptible to Rz at both the post-transcription and replication levels. These results are in accordance with those obtained by Li et al [28], who found that a dual-shRNA expression vector (AAV-157i/1694i), which coexpressed 2 shRNAs, targeted the S and X genes of HBV and reduced the levels of HBsAg, HBeAg, and HBV DNA by 87% ± 4%, 80.3% ± 2.6%, and 86.2% ± 7% respectively, at 8 days post-transduction. In a mouse model of prophylactic treatment, HBsAg and HBeAg were reduced to undetectable levels, and the serum HBV DNA level showed at least a 100-fold reduction.…”
Section: Discussionsupporting
confidence: 92%
“…Hence, HBV is assumed to be susceptible to Rz at both the post-transcription and replication levels. These results are in accordance with those obtained by Li et al [28], who found that a dual-shRNA expression vector (AAV-157i/1694i), which coexpressed 2 shRNAs, targeted the S and X genes of HBV and reduced the levels of HBsAg, HBeAg, and HBV DNA by 87% ± 4%, 80.3% ± 2.6%, and 86.2% ± 7% respectively, at 8 days post-transduction. In a mouse model of prophylactic treatment, HBsAg and HBeAg were reduced to undetectable levels, and the serum HBV DNA level showed at least a 100-fold reduction.…”
Section: Discussionsupporting
confidence: 92%
“…2) indicated that AAV-shRNA-1 had the greatest antiviral activity, with at least 90% inhibition efficiency at the replication, transcription, or translation level. Since single siRNA administration could be ineffective to inhibit pre-existing mutant HBV genomes 32 , the combination of multiple shRNAs targeting different HBV codon regions was suggested to overcome this problem and has yielded superior antiviral effects 33 . In the present study, the antiviral efficacy of AAV-shRNA-1 + 3 was 2-fold higher than that of a single AAV-shRNA at the DNA and protein levels, whereas a 5-fold higher efficacy was obtained at the RNA level with the use of a dual-shRNA vector.…”
Section: Discussionmentioning
confidence: 99%
“…The use of an adeno-associated virus (AAV) vector to simultaneously deliver two shRNAs targeting different HBV-related genes (157i targeting the HBV S gene and 1694i targeting the HBV X gene) has been demonstrated to result in greater antiviral effects than vectors that delivered a single shRNA in vitro and in vivo ( 19 ). In the present study, one or two shRNA expression cassettes were subcloned into a pLVX-shRNA1 vector ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, the requirement for alternative therapeutic approaches is urgent. Previous studies have suggested that two shRNAs that targeted the HBV S (157i) and X (1694i) genes may be employed to avoid the phenomenon of resistance of HBV mutants to a single siRNA ( 19 ). And the dual shRNA expression vector (AAV-157i-1694i) demonstrated greater antiviral effects in vitro and in vivo compared with those vectors only expressing a single shRNA ( 19 ).…”
Section: Discussionmentioning
confidence: 99%